Are gross job flows in Australia sensitive to exchange rate fluctuations?. (7th July 2008) - Mitchell, Bill; Myers, Jenny
This article considers whether rates of job destruction and creation are influenced by exchange rate movements. It shows that gross job flows in the goods-producing sector are significantly impacted by exchange rate fluctuations, with an appreciation increasing both job creation and destruction rates and hence job reallocation. However, job destruction does not dominate the adjustment process. Trading-services sector job destruction rate is marginally and negatively responsive to exchange rates, with the remaining-services sector unresponsive to exchange rate movements.